Screening of rhizobacteria from monkey pod trees for plant growth promoters and evaluating the antifungal potential of the biosynthesized selenium nanoparticles - Abu M. Babajide; Gboyega E. Adebami; Bukola C. Adebayo-Tayo (Scientific Reports)
Abstract Rhizobacteria, residing in the root zone of plants, are essential for enhancing plant growth and development and have recently been recognized for their role in nanoparticle synthesis. This study aims to isolate new strains of rhizobacteria from monkey pod trees, evaluate their potential as plant growth promoters, and assess their ability to synthesize selenium nanoparticles (SeNPs) with antifungal properties. The objectives include screening the isolates for phosphate solubilization potential, indolic compound production, nitrogen fixation, and SeNPs synthesis. The best-performing isolates were identified through molecular techniques, and the synthesized SeNPs were characterized and tested for antifungal activity. Out of 30 rhizobacterial strains screened, isolates RS3E and RS3F, identified as Lysinibacillus sphaericus and Bacillus amyloliquefaciens, respectively, showed significant phosphate solubilization (PSI ranging from 2.0 to 3.80 mm) and Indole Acetic Acid (IAA) production. The greenly synthesized SeNPs exhibited a maximum absorption at 262 nm, with scanning and transmission electron microscopy confirming their spherical nature and average particle size of 16.704 nm. Further validation of SeNPs synthesis was achieved using Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and energy dispersive X-ray (EDX) analysis. The SeNPs demonstrated excellent antifungal activity against Aspergillus niger and Aspergillus flavus, with inhibition zones ranging from 23.0 to 45.0 mm. This study highlights the potential of rhizobacteria-derived SeNPs as effective antifungal agents, offering a sustainable approach to fungal treatment in agriculture.